Rotpostvolym = stämplingslängd? - Andersson, Michael (SLU/School for Forest Management, 2012)
This work was conducted during spring and summer 2012 together with the company Uppsala Academy of Management as the principal. The two main objectives for the work are that: • Make a comparison between the measured volume in the standing forest and the measured volume at the industry on Uppsala Academy of Managements actual stumpage sale volume to see how well it conforms. • Examine if the buyers see any particular advantages or disadvantages of actual stumpage sale volume and what they think of Uppsala Academy of Managements actual stumpage sale volume and structure in general. I chose to use actual stumpage sale volume from the tree years 2009, 2010 and 2011 in my work. I divided the actual stumpage sale volume following four categories which was pine, spruce, pine/spruce and seed trees. After that I picked out sixteen actual stumpage sale volumes from each category to be a part of the work. When I selected the actual stumpage sale volume to be included in the work I contacted the buyers to get access to the measured volume. To make the study of the buyers opinion about Uppsala Academy of Managements actual stumpage sale volume and structure in general I sent out eight questions that I together with Uppsala Academy of Management decided. This work shows that the measured volume at the standing forest and the measured volume at the industry align very well with only a difference of 616 m3 solid wood under bark or 0.6 percent The responses received from the buyers to the questions I sent out can shortly be summarized with that the advantages of the actual stumpage sale volume is that they are fully planned and ready to be harvested. The disadvantage of the actual stumpage sale volume is that they often get expensive for the buyers.